Nutritional, immunological and microbiological profiles of burn patients - Barbosa, A. S. A. A.; Calvi, Sueli Aparecida [UNESP]; Pereira, Paulo Câmara Marques [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2009)
A burn is a lesion on an organic tissue resultant from direct or indirect action of heat on the organism. The present study aimed to evaluate the nutritional, immunological and microbiological status of burn patients at the Bauru State Hospital, São Paulo state, Brazil, in 2007. Eight patients, aged more than 18 years and injured up to 24 hours, were evaluated at the moment of hospitalization and seven days later. All victims were males with a mean age of 38 years. on average, 17.5% of their body surfaces were burned and 50% of the patients were eutrophic. There were significant alterations in levels of erythrocytes, hemoglobin, hematocrit, total protein and albumin due to increased endothelial permeability, direct destruction of proteins in the heat-affected area and blood loss from lesions or debridement. At a second moment, cytokines IL-6 and TNF-alpha had augmented significantly, with IL-6 presenting elevated levels in relation to controls at the first moment. Microbiological analysis showed that 100% of the samples collected at hospital admission were negative and after one week Staphylococcus aureus was found in all cultures. Therefore, a burn patient may be considered immunosuppressed and these results indicate significant nutritional, immunological and microbiological alterations that can interfere in his recovery.
Keywords: burn; nutrition; infection; TNF-alpha; IL-6; laboratory exams